The impact of FDI on haze pollution: “Pollution paradise” or “pollution halo?”–Spatial analysis of PM2.5 concentration raster data in 283 cities - Liu, Yanbo; Guo, Mingshun (Frontiers in Environmental Science, 2023)
This paper constructs a spatial econometric model based on the environmental Kuznets curve to examine the effect of foreign direct investment (FDI) on urban haze pollution in Chinese cities. The evidence from the raster data of PM2.5 concentration in MODIS and MISR shows that there is a significant spatial correlation between haze pollution and FDI in Chinese cities, which is expressed as a spatial spillover effect; FDI in Chinese mainland cities reduces haze pollution, which confirms the "pollution halo hypothesis";using instrumental variable estimation, the above conclusions are still robust; The total effect of FDI on haze pollution is negative, and the total effect can be decomposed into scale effect, technology effect and structural effect;FDI increases urban haze pollution through scale effects and structural effect, but decreases urban haze pollution through technology effects; the environmental Kuznets curve exists in urban haze pollution in China, i.e., there is an inverted "U" relationship between economic development and haze pollution. This paper proposes that the establishment of inter-city linkage mechanism of haze control and the full play of the technical effect of FDI on haze pollution will help reduce urban haze pollution.